Overview of Breast Care Knowledge in Pregnant Women in the Third Trimester at Midwife's Independent Practice : A Case Study at PMB Anisa Mauliddina, Yogyakarta, Indonesia - Ika Pratidina, Almira; Puspitasari, Elika (Buletin Ilmu Kebidanan dan Keperawatan, 2023)
Breast care during late pregnancy is an effort to facilitate breastfeeding and prevent issues that may arise during nursing, such as sore nipples, cracked skin, swollen breasts, and blocked milk ducts. This ensures that when the baby is born, the breasts can function effectively when needed. This research aims to assess the knowledge of breast care among third-trimester pregnant women. The research method employed is descriptive research with a cross-sectional approach. The population for this study consists of pregnant women who underwent antenatal care (ANC) examinations at PMB Anisa Mauliddina during February 2023, totalling 54 individuals. The sampling technique used was total sampling. The research findings indicate that most respondents are aged between 20 and 35, accounting for 47 respondents (87%). Regarding educational background, most respondents had attended college, with 20 respondents (37%), while the majority of respondents were not employed (homemakers), totalling 26 respondents (48.1%). Regarding knowledge, 48 respondents (88.9%) were classified as having good knowledge, while six respondents (11.1%) had sufficient knowledge. Among the age groups, the highest percentage of respondents with good knowledge were those aged 20 to 35, comprising 42 respondents (87.5%). Based on educational background, 19 respondents with a college education had good knowledge and based on employment status, 22 respondents who were not employed (homemakers) possessed good knowledge (45.8%). The results of this research can serve as a basis for comparison in future studies.